2021
DOI: 10.4049/jimmunol.2100440
|View full text |Cite
|
Sign up to set email alerts
|

An IRF4–MYC–mTORC1 Integrated Pathway Controls Cell Growth and the Proliferative Capacity of Activated B Cells during B Cell Differentiation In Vivo

Abstract: Cell division is an essential component of B cell differentiation to Ab-secreting plasma cells, with critical reprogramming occurring during the initial stages of B cell activation. However, a complete understanding of the factors that coordinate early reprogramming events in vivo remain to be determined. In this study, we examined the initial reprogramming by IRF4 in activated B cells using an adoptive transfer system and mice with a B cell–specific deletion of IRF4. IRF4-deficient B cells responding to influ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 99 publications
1
15
0
Order By: Relevance
“…IRF4 is a transcription factor lowly expressed in naïve cells, absent in GC B cells and upregulated in plasma cells (Willis et al, 2014 ). In particular, IRF4 has been shown to be important for regulating the proliferative capacity of B cells during activation and is required for early GC B cells formation in a B cell‐intrinsic manner (Patterson et al, 2021 ; Willis et al, 2014 ). Thus, the lower expression of IRF4 by B cells from older donors may result in early proliferative defects, as previously reported (Blaeser et al, 2008 ) and contribute to the reduced early GC response, as we observed in our mouse studies.…”
Section: Discussionmentioning
confidence: 99%
“…IRF4 is a transcription factor lowly expressed in naïve cells, absent in GC B cells and upregulated in plasma cells (Willis et al, 2014 ). In particular, IRF4 has been shown to be important for regulating the proliferative capacity of B cells during activation and is required for early GC B cells formation in a B cell‐intrinsic manner (Patterson et al, 2021 ; Willis et al, 2014 ). Thus, the lower expression of IRF4 by B cells from older donors may result in early proliferative defects, as previously reported (Blaeser et al, 2008 ) and contribute to the reduced early GC response, as we observed in our mouse studies.…”
Section: Discussionmentioning
confidence: 99%
“…4E). Sustained and high Irf4 expression was shown to promote PC differentiation while antagonizing the GC path [26], a mechanism that requires IRF4‐induced MYC target genes [27]. In agreement with Irf4 downregulation, Myc expression was significantly decreased in CD19 + cells (p = 0.0087), and its target genes Cdc25a and Ccnd2 were downregulated with citrulline diet (p = 0.0284 for Cdc25a and p = 0.0519 for Ccnd2 expression; Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The CTY dilution profiles of cells transduced with sgRNAs targeting Prdm1 and Plpp5 overlapped with the untransduced controls, indicating that these genes do not influence B cell proliferation ( Figure 3B ) . It has previously been demonstrated that Irf4 -deficient B cells have a reduced proliferative capacity in response to LPS compared to WT B cells ( 27 , 36 ). This proliferative defect was confirmed by our data and was most notable at later timepoints where cells transduced with Irf4 targeting sgRNAs had stalled in their proliferation ( Figure 3B ) .…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with the differentiation results demonstrated that some of these genes ( Irf4 , Hspa5 and Sec61a1 ) affected both cell number and differentiation, while the other genes identified only influenced cell number ( Supplementary Figure 2B ). Irf4 has been linked to cell division in activated B cells as it directly induces the expression of genes involved in proliferation, including Myc ( 27 , 28 ). Sumo2 has previously been implicated in proliferation and cell survival as Sumo2-deficient mouse embryonic fibroblasts have decreased cell cycling and an increased cell death compared to WT cells ( 29 ).…”
Section: Resultsmentioning
confidence: 99%